Expanding the Toolbox of Upconversion Nanoparticles for In Vivo Optogenetics and Neuromodulation - All, Angelo Homayoun; Zeng, Xiao; Teh, Daniel Boon Loong; Yi, Zhigao; Prasad, Ankshita; Ishizuka, Toru; Thakor, Nitish; Hiromu, Yawo; Liu, Xiaogang (Advanced materials (Weinheim), 2019)
Optogenetics is an optical technique that exploits visible light for selective neuromodulation with spatio‐temporal precision. Despite enormous effort, the effective stimulation of targeted neurons, which are located in deeper structures of the nervous system, by visible light, remains a technical challenge. Compared to visible light, near‐infrared illumination offers a higher depth of tissue penetration owing to a lower degree of light attenuation. Herein, an overview of advances in developing new modalities for neural circuitry modulation utilizing upconversion‐nanoparticle‐mediated optogenetics is presented. These developments have led to minimally invasive optical stimulation and inhibition of neurons with substantially improved selectivity, sensitivity, and spatial resolution. The focus is to provide a comprehensive review of the mechanistic basis for evaluating upconversion parameters, which will be useful in designing, executing, and reporting optogenetic experiments. Optogenetics generally utilizes visible light to modulate opsins in targeted neurons but with poor penetration to deep tissues. Upconversion nanoparticle (UCNP)‐mediated NIR optogenetics offers an attractive alternative due to the improved depth of tissue penetration. The basic principles and feasibility of UCNPs for NIR optogenetics are discussed together with a critical survey of the latest developments in the field.